Accuracy of Reservoir Predictions for the Nesjavellir Geothermal Field, Iceland - Bodvarsson, G. S.; Gislason, G.; Gunnlaugsson, E.; Sigurdsson, O.; Stefansson, V.; Steingrimsson,B. (Lawrence Berkeley National Laboratory, 1993)
The performance of the 1986 three-dimensional numerical model of the Nesjavellir geothermal field for predicting the deliverabilities and pressure decline of the wells during the period 1987 through 1991 is investigated. The model predicted adequately the flow rate and enthalpy transients of most wells, but overpredicted the pressure decline by 3 to 4 bars.